Online learner competencies : knowledge, skills, and attitudes for successful learning in online settings - Beaudoin, Michael F. (IBSTPI book series., 2013)
The book identifies a set of validated competencies and performance statements, withsupporting explanation and data to inform and equip online learners with the critical attitudes, knowledge and skills for successful learning in online and/or blended learning settings. The work also enables online education providers (e.g., instructors, course designers, program administrators, scholars) to better understand learner needs in order to design and deliver online education products and services best suited to learners. Supplementing a large number of anecdotally-based "how to" books published for those engaged in online education, this volume offers a definitive set of 14 competencies and 75 performance statements (that demonstrate those competencies). Validated by systematic research and input from over 1,000 online users and providers worldwide, this work should impact the quality of learning and teaching at both the individual and organizational levels, involved in online education.